2022
DOI: 10.1111/jav.02958
|View full text |Cite
|
Sign up to set email alerts
|

Defining moults in migratory birds: a sequence‐based approach

Abstract: Two broad nomenclatures have emerged to describe moult strategies in birds, the 'lifecycle' system which describes moults relative to present-day breeding and other lifehistory events, and the Humphrey-Parkes (H-P) system which reflects the evolution of moults along ancestral lineages. Using either system, challenges have arisen defining strategies in migratory species with more than one moult per year. When all or part of two moults occur in non-breeding areas, extra moults may fail to be recognized or they m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 149 publications
(16 citation statements)
references
References 38 publications
0
16
0
Order By: Relevance
“…Howell et al . 2003, Pyle 2008, 2022, Johnson & Wolfe 2017). This terminology simulates a more exact system, but with the exactness comes increased complexity.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Howell et al . 2003, Pyle 2008, 2022, Johnson & Wolfe 2017). This terminology simulates a more exact system, but with the exactness comes increased complexity.…”
Section: Figurementioning
confidence: 99%
“…H-P terminology is commonly used in the New World (Palmer 1976, Ginn & Melville 1983, and it can better describe complicated moult cycles, especially when terminology adjustments that were more recently introduced are used (e.g. Howell et al 2003, Pyle 2008, 2022, Johnson & Wolfe 2017. This terminology simulates a more exact system, but with the exactness comes increased complexity.…”
mentioning
confidence: 99%
“…For example, Pyle et al (2020) found that the ratio of yearlings to older individuals among boreal forest birds indicated the older birds exclude yearlings from preferred breeding habitats through despotism, a dynamic that could inform habitat management. Understanding molt strategies is, in turn, critical to age determination, but for many North American species that molt away from their breeding grounds, these strategies are poorly known (Pyle 1997a, 2022a, Pyle et al 2009, 2018a. Fitness consequences and factors driving the evolution of molt, such as migration distance and habitats, have also been understudied because of lack of detailed information for most species and differing opinions on the definition of molts that occur away from breeding grounds (Pyle 2022a).…”
Section: Hawaii Observations March 2021 To January 2022mentioning
confidence: 99%
“…Understanding molt strategies is, in turn, critical to age determination, but for many North American species that molt away from their breeding grounds, these strategies are poorly known (Pyle 1997a, 2022a, Pyle et al 2009, 2018a. Fitness consequences and factors driving the evolution of molt, such as migration distance and habitats, have also been understudied because of lack of detailed information for most species and differing opinions on the definition of molts that occur away from breeding grounds (Pyle 2022a).…”
Section: Hawaii Observations March 2021 To January 2022mentioning
confidence: 99%
See 1 more Smart Citation